Cognizing and characterizing the organic phosphorus in lake sediments: Advances and challenges. (15th July 2022) - Ni, Zhaokui; Li, Yu; Wang, Shengrui
Highlights: A review about current understanding and characterizing sediments OP is provided. Sediment OP is essential to internal P loading and algal bloom. OP transformation needs to be deduced by both composition and molecular size change. Develop direct, high-sensitivity and combined methods can enhance OP characterization. Composite index based molecular properties and degradability is better reflect OP bioavailability. Abstract: Organic phosphorus (OP) is one of the main forms of phosphorus in lake ecosystems. Mounting evidence has shown that sediment OP has become a major but underestimated issue in addressing lake eutrophication and algal bloom. However, a holistic view of sediment OP remains missing. This review aims to provide an overview of progress on the studies of OP in lake sediments, focusing on the contribution of OP to internal P loading, its potential role in algal bloom, and the migration and transformation. In addition, this work systematically summarized current methods for characterizing OP content, chemical fraction, composition, bioavailability, and assessment of OP release in sediment, with the pros and cons of each method being discussed. In the end, this work pointed out following efforts needed to deepen the understanding of sediment OP, namely: (1) In-depth literature review from a global perspective regarding the contribution of sediment OP to internal P loading with further summary about its pattern of distribution, accumulation and historical changes; (2) better mathematical models for describing drivers and the linkages between the biological pump of algal bloom and the replenishment of sediment OP; (3) fully accounting the composition and molecular size of OP for better understanding its transformation process and mechanism; ; (4) developing direct, high-sensitivity and combined techniques to improve the precision for identifying OP in sediments; (5) establishing the response of OP molecular properties and chemical reactivity to OP biodegradability and designing a comprehensive and accurate composite index to deepen the understanding for the bioavailability of OP; and (6) integrating fundamental processes of OP in current models to better describe the release and exchange of P in sediment-water interface (SWI). This work is expected to provide critical information about OP properties and deliver perspectives of novel characterization methods. Graphical abstract: Image, graphical abstract